Implementation Determination Limit Value Dependent Rights Objects by Sellers in Auctions Execution Dependent Rights - Nizla Rohaya; Upik Mutiara; Ade Novensia Arahman (Jurnal Hukum Volkgeist, 2022)
This research is motivated by the author submitting an application against a lawsuit related to the determination of the estimated value limit that is not in accordance with applicable regulations, causing losses to the debtor. The purpose of this study is to determine the auction mechanism and the application of determining the value of the mortgage object by the seller. This research is based on the normative legal research method through a legal approach. The results of this study are that the auction mechanism for the execution of mortgage objects through the State Assets and Auction Service Office must comply with the rules in the Regulation of the Minister of Finance Number 213/PMK.06/2020 concerning Auction Implementation Guidelines. The implementation of the determination of the boundary of the mortgage object in the field has not been in accordance with the procedure and legal protection for the debtor has not been maximized because it can only be done through a lawsuit in court and the State Assets and Auction Service Office does not have the authority to conduct an auction against the applicable boundary determination. Suggestions for the Government to change the method of setting boundaries, which previously had 2 (two) methods, namely an assessment to avoid losses suffered by debtors and provide more legal benefits for debtors.